Objective Identification of Intermediate Lesions Inducing Myocardial Ischemia Using Sequential Intracoronary Pressure and Flow Measurements - Valérie E. Stegehuis; Gilbert W. M. Wijntjens; Sukhjinder S. Nijjer; Guus A. de Waard; Tim P. van de Hoef; Sayan Sen; Ricardo Petraco; Mauro Echavarría‐Pinto; Martijn Meuwissen; Ibrahim Danad; Paul Knaapen; Javier Escaned; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Although ischemic heart disease has a complex and multilevel origin, the diagnostic approach is mainly focused on focal obstructive disease as assessed by pressure‐derived indexes. The prognostic relevance of coronary flow over coronary pressure has been suggested and implies that identification of relevant perfusion abnormalities by invasive physiology techniques is critical for the correct identification of patients who benefit from coronary revascularization. The purpose of this study was to evaluate the diagnostic potential of a sequential approach using pressure‐derived indexes instantaneous wave‐free ratio (iFR), fractional flow reserve (FFR), and coronary flow reserve (CFR) measurements to determine the number of intermediate lesions associated with flow abnormalities after initial pressure measurements. Methods and Results A total of 366 intermediate lesions were assessed with simultaneous intracoronary pressure and flow velocity measurements. Contemporary clinical iFR, FFR, and CFR cut points for myocardial ischemia were applied. A total of 118 (32%) lesions were FFR+ and 136 (37%) lesions were iFR+. Subsequent CFR assessment resulted for FFR in a total of 91 (25%) FFR+/CFR+ and for iFR a total of 111 (30%) iFR+/CFR+ lesions. An iFR, FFR, and invasive flow velocity assessment approach would have yielded 20% of lesions (74 of 366) as ischemic. Conclusions Ultimately, 20% of intermediate lesions are associated with flow abnormalities after applying a pressure and flow velocity sequential approach. If iFR is borderline, FFR has limited additional value, in contrast with CFR. These results emphasize the use of coronary physiology in assessing stenosis severity but may also further question the contemporary reputation of a pressure‐based approach as a gold standard for the detection of myocardial ischemia in ischemic heart disease.